NF-κB-inducing kinase maintains T cell metabolic fitness in antitumor immunity - Gu, Meidi; Zhou, Xiaofei; Sohn, Jee Hyung; Zhu, Lele; Jie, Zuliang; Yang, Jin-Young; Zheng, Xiaofeng; Xie, Xiaoping; Yang, Jie; Shi, Yaoyao; Brightbill, Hans D.; Kim, Jae Bum; et al. (Nature immunology, 2021)
Metabolic reprograming toward aerobic glycolysis is a pivotal mechanism shaping immune responses. Here we show that deficiency in NF-κB-inducing kinase (NIK) impairs glycolysis induction, rendering CD8 + effector T cells hypofunctional in the tumor microenvironment. Conversely, ectopic expression of NIK promotes CD8 + T cell metabolism and effector function, thereby profoundly enhancing antitumor immunity and improving the efficacy of T cell adoptive therapy. NIK regulates T cell metabolism via a NF-κB-independent mechanism that involves stabilization of hexokinase 2 (HK2), a rate-limiting enzyme of the glycolytic pathway. NIK prevents autophagic degradation of HK2 through controlling cellular reactive oxygen species levels, which in turn involves modulation of glucose-6-phosphate dehydrogenase (G6PD), an enzyme that mediates production of the antioxidant NADPH. We show that the G6PD–NADPH redox system is important for HK2 stability and metabolism in activated T cells. These findings establish NIK as a pivotal regulator of T cell metabolism and highlight a post-translational mechanism of metabolic regulation. Metabolic rewiring of cytotoxic T lymphocytes (CTLs) can impair their antitumor functions. Sun and colleagues demonstrate that CTL-intrinsic activity of the kinase NIK is essential for CTL metabolic fitness in the tumor microenvironment.